121k views
2 votes
Simplify (x + y + 3)(x + y - 4)

User Luison
by
5.1k points

2 Answers

6 votes

Answer:

x²+2xy-x+y²-y-12

Explanation:

(x+y+3)(x+y-4)

= x(x+y-4)+y(x+y-4)+3(x+y-4)

= x²+xy-4x+xy+y²-4y+3x+3y-12

= x²+2xy-x+y²-y-12

User Brysgo
by
5.3k points
0 votes

Hello!

The answer is:

The simplified expression is:


(x + y + 3)(x + y - 4)=x^(2) +y^(2) +2xy-x-y-12

Why?

To solve the problem, we need to remember how to use the distributive property and how to add like terms.

The distributive property can be defined as follow:


(a+b)(c+d)=ab+ad+bc+bd

The like terms are the terms that share the same variable and the same exponent, for example:


3x+x+ x^(2)=x^(2) +4x

We were able to add the first and the second term because they share the same variable and the same exponent.

Now, we are given the expression:


(x+y+3)(x+y-4)

So, simplifying we have:


(x + y + 3)(x + y - 4)=(x*x)+(x*y)-(4*x)+(y*x)+(y*y)-(4*y)+(3*x)+(3*y)-(3*4)\\\\(x + y + 3)(x + y - 4)=x^(2) +xy-4x+xy+y^(2)-4y+3x+3y-12\\\\(x + y + 3)(x + y - 4)=x^(2) +y^(2) +2xy-x-y-12

Hence, we have that the simplified expression is:


(x + y + 3)(x + y - 4)=x^(2) +y^(2) +2xy-x-y-12

Have a nice day!

User Shloime Rosenblum
by
5.5k points